Estabilidade de edifícios de concreto pré-moldado com ligações semirrígidas - Meireles Neto, Marcelo (2012)
The material and geometric nonlinearity has a strong influence on the structural stability of precast concrete buildings with semi-rigid connections. However, most studies about the global stability of such buildings are based on linear analyses, with the nonlinear effects being evaluated using approximate methods. Therefore, this work aims to assess the effect of the connection stiffness in the stability of precast concrete plane frames considering the geometric and material nonlinearities. The semi-rigid connections are modeled using a connection element developed and implemented in this work. The geometric nonlinearity due to large displacements is accounted for using plane frame elements based on the co-rotational formulation. The material nonlinearity is considered using the steel and concrete stress-strain curves of the NBR 6118:2003 standard. The stress integration is carried-out using the fiber method, implemented in this work. The formulations and implementations performed in this work were verified and validated using results available in the literature. After that, the influence of the connection stiffness on the global stability was studied using linear and nonlinear analyses. The results showed that the increase of connection stiffness greatly reduced the lateral displacementsand the second-order effects of precast concrete frames, indicating that semi-rigid connections are an alternative to avoid stability problems of precast concrete frames. It was also concluded that the parameter γz generally leads to accurate displacements and bending moments, especially for frames with high stiffness connections.